TRADE OPENNESS AND INDUSTRIAL OUTPUT GROWTH IN NIGERIA - Ilemona, Adofu; Adejoh, Mark Ojonugwa (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2021)
The study assessed trade openness and industrial output growth in Nigeria spanning the period of 1986 to 2019. Using the new trade theory as theoretical premise, the study sought to determine the whether trade openness causes industrial output growth in Nigeria. To do this, the study used the Toda-Yamamoto (T-Y) causality procedure. Using Nigeria’s industrial output as proxy for industrial output growth and trade-to-GDP ratio as proxy for trade openness, findings from the T-Y estimation revealed that there was no causal relationship between trade openness and industrial output growth in the country. Thus, the study concluded that trade openness did not cause industrial output growth in Nigeria for the period under analysis. To ensure that trade openness leads to industrial output growth, the study recommends that trade in the country would have to be further opened up so as to allow for import discipline which would drive competition and promote the growth of Nigeria’s industrial sector